Laughter in the Dark: Egypt to the Tune of Change: An extract - El Rashidi, Yasmine (New Agenda: SA Journal of Social and Economic Policy, 2024)
The modern history of Egypt is told, by insiders and outsiders alike, largely through the narrative of authoritarian leaders and their so-called “iron-fisted” rule. Gamal Abdel Nasser (1956–1970) was well known for his method of having people disappeared – “behind the sun” is the Arabic refrain1 – if they disagreed with his socialist, nationalist policies, as well as for his persecution of Egypt’s Jews.2 And for thirty years, under the rule of the late Hosni Mubarak (1981–2011), citizens did not dare speak of politics, for fear of the deep state, with its troops of secret police and informants, notorious for their ruthless methods of kidnapping and torture.